Initial pulp changes during orthodontic movement: histomorphological evaluation - Santamaria Jr.,Milton (2007)
This study evaluated pulp changes in molars of rats submitted to tooth movement by application of a 0.4 N force. Twenty-five adult male Wistar rats (Rattus norvegicus, albinus) were randomly assigned to 5 groups (n=5), being one control group not submitted to force application, and four study groups of 6, 12, 24 and 72 h of force application. The study groups received a 5-mm long nickel-titanium closed coil spring, placed from the right maxillary first molar to the maxillary incisors of each animal. The coil spring was used for mesial inclination of the first molar. After the specific period of tooth movement of each study group, the animals were sacrificed and specimens containing the teeth submitted to movement were processed and stained with hematoxylin and eosin for histological analysis under light microscopy. The results demonstrated alteration of the odontoblastic layer, with hypertrophy of odontoblasts especially at the mesial area of the coronal pulp, edema of the pulp connective tissue in the central area of the pulp, and vascular alteration with accumulation of erythrocytes and leukocytes inside the vessels, especially at the mesial root of the moved teeth. These changes were less remarkable for the 72-h period. Thus, it may be concluded that tooth movement yielded pulpal tissue alterations compatible with an inflammatory process, which are reversible if the aggression is not more intense than the physiological limit of tissue tolerance.